Measurement of the prompt-production cross-section ratio σ(χc2)/σ(χc1) in pPb collisions at √sNN=8.16 TeV - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2021)
This article reports the first measurement of prompt χc1 and χc2 charmonium production in nuclear collisions at Large Hadron Collider energies. The cross-section ratio σ(χc2)/σ(χc1) is measured in pPb collisions at √sNN=8.16 TeV, collected with the LHCb experiment. The χc1,2 states are reconstructed via their decay to a J/ψ meson, subsequently decaying into a pair of oppositely charged muons, and a photon, which is reconstructed in the calorimeter or via its conversion in the detector material. The cross-section ratio is consistent with unity in the two considered rapidity regions. Comparison with a corresponding cross-section ratio previously measured by the LHCb Collaboration in pp collisions suggests that χc1 and χc2 states are similarly affected by nuclear effects occurring in pPb collisions.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Titel sind "c2" und "c1" tiefgestellt
LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, M. Dziewiecki, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, H. Malygina, J. Marks, N. Meinert, A.B. Morris, S. Neubert, A. Piucci, M. Schmelling, S. Stemmle, D.J. Unverzagt, U. Uwer, H. Viemann, R. Waldi, C. Wang, L. Witola, M. Zavertyaev, A. Zhelezov, und weitere 933
Gesehen am 20.08.2021